Tle4z1 Facilitate the Male Sexual Differentiation of Chicken Embryos - Chen, Chen; Zhou, Shujian; Lian, Ziyi; Jiang, Jingyi; Gao, Xiaomin; Hu, Cai; Zuo, Qisheng; Zhang, Yani; Chen, Guohong; Jin, Kai; Li, Bichun (Frontiers in Physiology, 2022)
Background: Sex differentiation is a complex and precisely regulated process by multiple genes in chicken. However, it is still unclear on the key genes of sex differentiation. Objective: To explore the function of Tle4z1 screened by RNA-seq sequencing on sex differentiation during the development of chicken embryos. Methods: Tle4z1 was differentially expressed from the RNA-seq of ESCs and PGCs in male and female chickens. Then, we established an effective method to overexpression or knocking down the expression of Tle4z1 in ovo and in vitro, respectively. Histomorphological observation, qRT-PCR and ELISA were applied to detect the function of Tle4z1 in the process of male sex differentiation by injecting vectors into embryos at day 0. Results: It showed that Tle4z1 has significant male preference in embryonic day 4.5, such phenomenon persisted during the growth period of chicken embryos. Morphological observation results showed that the gonads on both sides of genetic male (ZZ) embryos with Tle4z1 knocking down developed asymmetrically, the gonadal cortex became thicker showing the typical characteristics of genetic female (ZW) gonads. Furthermore, the expression of Cyp19a1, which dominates female differentiation, was significantly increased, while the expression of male marker genes Dmrt1, Sox9, WT1 and AR was significantly downregulated. In addition, the concentration of testosterone also significantly decreased, which was positively correlated with the expression of Tle4z1 (P < 0.01). Conversely, the ZW embryo showed defeminized development when Tle4z1 was overexpressed. Conclusion: We prove that the Tle4z1 is a novel gene through the male sexual differentiation via gene regulation process and synthesis of testosterone, which construct the basis for understanding the molecular mechanism of sex differentiation in chickens.